Bamboo diversity, ecological structure, and utilization in the riparian ecosystem of the upper Bengawan Solo River, Central Java, Indonesia - FIKA NUR APRILIA; FRANSISCA AMELIA KARTIKA ARDHYANTI; GHAZY AQILA SHANDY PRABOWO; HANA PARAMESTI; ANA SHOLEKAH ASZAR; CHEE KONG YAP; AHMAD DWI SETYAWAN (Nusantara Bioscience, 2025)
Abstract. Aprilia FN, Ardhyanti FAK, Prabowo GAS, Paramesti H, Aszar AS, Yap CK, Setyawan AD. 2025. Bamboo diversity, ecological structure, and utilization in the riparian ecosystem of the upper Bengawan Solo River, Central Java, Indonesia. Nusantara Bioscience 17: 259-276. Bamboo plays an important ecological and socio-economic role in tropical riparian landscapes, yet its spatial structure and environmental determinants remain poorly quantified. This study analyzed the diversity, composition, ecological dominance, and utilization of bamboo communities along the upstream–midstream–downstream gradient of the upper Bengawan Solo River, Central Java, Indonesia. Field surveys recorded five species—Bambusa spinosa, Dendrocalamus asper, Gigantochloa apus, G. atter, and G. atroviolacea—distributed unevenly across riparian zones. Diversity, species richness, and structural heterogeneity increased downstream, shifting from monodominant B. spinosa stands upstream to multi-species Gigantochloa assemblages in lowland alluvial areas. Importance Value Index (IVI) patterns revealed strong environmental filtering in the upstream zone, mixed natural–managed dominance midstream, and cultivation-enhanced coexistence downstream. Pearson correlation analysis indicated that soil moisture, canopy openness, and soil pH were the strongest predictors of diversity, whereas species dominance was shaped primarily by ecological traits and management intensity. Utilization patterns reflected a biocultural continuum, with D. asper and Gigantochloa spp. providing multipurpose materials for construction, food, handicrafts, and cultural practices, while B. spinosa served chiefly as an ecological stabilizer in upland slopes. The riparian bamboo system represents a socio-ecological mosaic shaped by hydrological gradients and community management. These findings highlight bamboo’s potential as a nature-based solution for riparian stabilization, biodiversity conservation, and livelihood support. Strengthening integrated, community-based bamboo management could enhance ecological resilience and sustainable riverine landscape governance in tropical regions.